2015
DOI: 10.1242/dev.119891
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific roles of Fgfr2 in development of the external genitalia

Abstract: Congenital anomalies frequently occur in organs that undergo tubulogenesis. Hypospadias is a urethral tube defect defined by mislocalized, oversized, or multiple openings of the penile urethra. Deletion of Fgfr2 or its ligand Fgf10 results in severe hypospadias in mice, in which the entire urethral plate is open along the ventral side of the penis. In the genital tubercle, the embryonic precursor of the penis and clitoris, Fgfr2 is expressed in two epithelial populations: the endodermally derived urethral epit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 58 publications
0
36
0
Order By: Relevance
“…Fgf signaling also is important in genital development and sexual differentiation (40,(44)(45)(46). Our experiments revealed that Fgf9, Fgfr2, and Fgfr3 expression is diminished by prenatal exposure to flutamide, but Fgf9 and Fgfr2 show no response to neonatal exposure to estrogen.…”
Section: Discussionmentioning
confidence: 64%
“…Fgf signaling also is important in genital development and sexual differentiation (40,(44)(45)(46). Our experiments revealed that Fgf9, Fgfr2, and Fgfr3 expression is diminished by prenatal exposure to flutamide, but Fgf9 and Fgfr2 show no response to neonatal exposure to estrogen.…”
Section: Discussionmentioning
confidence: 64%
“…Urethral closure and differentiation of the phallus are under the regulation of complex gene networks. In mice, fibroblast growth factor 10 (FGF10) and its receptor fibroblast growth factor receptor 2 isoform IIIb (FGFR2IIIb) positively regulate genital tubercle (GT) outgrowth (Haraguchi et al 2000, Satoh et al 2004, Petiot et al 2005, Gredler et al 2015, Harada et al 2015. Deletion of Fgf10 or Fgfr2IIIb results in abnormal urethra formation (Haraguchi et al 2000, Satoh et al 2004, Petiot et al 2005, Gredler et al 2015, Harada et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…In mice, fibroblast growth factor 10 (FGF10) and its receptor fibroblast growth factor receptor 2 isoform IIIb (FGFR2IIIb) positively regulate genital tubercle (GT) outgrowth (Haraguchi et al 2000, Satoh et al 2004, Petiot et al 2005, Gredler et al 2015, Harada et al 2015. Deletion of Fgf10 or Fgfr2IIIb results in abnormal urethra formation (Haraguchi et al 2000, Satoh et al 2004, Petiot et al 2005, Gredler et al 2015, Harada et al 2015. FGF10, acting via the FGFR2IIIb receptor (Ornitz et al 1996, Zhang et al 2006, may direct epithelium-mesenchymal crosstalk and regulate GT patterning and urethral closure (Satoh et al 2004, Gredler et al 2015, Harada et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The significance of the ectoderm has been clearly shown in an elegant study from Cohn’s group demonstrating that the contact between ectodermal and endodermal epithelia, i.e., the formation of the cloacal membrane, is crucial for GT initiation (Seifert et al, 2009b). The ectoderm’s importance in signaling regulation is also demonstrated by the fact that GT malformations are observed in ectoderm-specific Fgfr2 (Gredler et al, 2015) and Smoothened (Seifert et al, 2009a) conditional knockout animals. The authors of these papers also noted that the ventral ectoderm, along with the underlying cloacal epithelium, might also play a structural role possibly regulated by HH or FGF signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic mechanisms involved in this early androgen-independent phase of genital development are not yet fully understood. Nonetheless, investigations using knockout mouse models have demonstrated that the canonical Wnt (Lin et al, 2008; Miyagawa et al, 2009), Fgf (Gredler et al, 2015; Haraguchi et al, 2000; Lin et al, 2013; Petiot et al, 2005; Seifert et al, 2009b), Bmp (Suzuki et al, 2003) and Shh (Haraguchi et al, 2001; Lin et al, 2009; Miyagawa et al, 2009; Perriton et al, 2002; Seifert et al, 2009a; Seifert et al, 2010) signaling pathways are involved in the initiation and continuous development of the GT. Before e14.5 (Suzuki et al, 2002) GT development is identical in both sexes.…”
Section: Introductionmentioning
confidence: 99%